2020
DOI: 10.1021/acs.jpcc.0c04902
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Effects of NH3 on SO2 Poisoning for In Situ Removal of Metal Sulfates in Low-Temperature NH3-SCR over an Fe–V Catalyst

Abstract: SO2 poisoning is a significant challenge for low-temperature selective catalytic reduction of NO x with NH3. Fundamental understanding of such sulfation effects on the catalyst is an essential step for finding strategies to overcome the issue. Here, the effect of NH3 on the temperature-driven sulfation process is systematically investigated over an Fe–V catalyst composed of α-Fe2O3 and FeVO4. When poisoning occurred by SO2 + O2, the highly dispersed and thermally stable Fe2(SO4)3 species would be formed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Here, several possible directions and methods for follow-up research are proposed. It is hard to maintain appropriate sulfate content over metal oxides without continuous decompositions or accumulations during the reaction. In situ SO 2 sulfation treatment effectively prevented the conversion of surface sulfates to bulk sulfates and maintained the interfacial effects with an appropriate sulfate content. , CeO 2 –SiO 2 and CeO 2 –ZrO 2 catalysts were fabricated with the characteristics of high surface area and moderate sulfate storage to make full use of the adsorption and activation characteristics of sulfates. Besides, simple N 2 /Ar/NH 3 thermal treatment was proved to eliminate sulfates without affecting the surface area and redox characteristics over specific CeO 2 and Fe 2 O 3 catalysts. The synergistic catalysis between acid and metal sites and the interfacial effect caused by sulfates were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, several possible directions and methods for follow-up research are proposed. It is hard to maintain appropriate sulfate content over metal oxides without continuous decompositions or accumulations during the reaction. In situ SO 2 sulfation treatment effectively prevented the conversion of surface sulfates to bulk sulfates and maintained the interfacial effects with an appropriate sulfate content. , CeO 2 –SiO 2 and CeO 2 –ZrO 2 catalysts were fabricated with the characteristics of high surface area and moderate sulfate storage to make full use of the adsorption and activation characteristics of sulfates. Besides, simple N 2 /Ar/NH 3 thermal treatment was proved to eliminate sulfates without affecting the surface area and redox characteristics over specific CeO 2 and Fe 2 O 3 catalysts. The synergistic catalysis between acid and metal sites and the interfacial effect caused by sulfates were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Various characterization results indicated that sulfates would not commonly combine with V 2 O 5 domains because of the relatively weak binding energy between sulfates and V 2 O 5 compared to other metal oxides like CeO 2 , Fe 2 O 3 , TiO 2 , , etc. Baraket et al reported that sulfates broadened the operating temperature window of V 2 O 5 /TiO 2 to the range of 300 and 400 °C.…”
Section: Metal Oxide Catalystsmentioning
confidence: 99%
“…According to the results, the apparent activation energy ( E a ) of Cu 0.75 Mn 2.25 O 4 -NH (36.4 kJ·mol –1 ) is obviously lower than that of Cu 0.75 Mn 2.25 O 4 -NP (70.9 kJ·mol –1 ). This illustrates that the nanostructure could reduce the reaction barriers and improve the catalytic performance. , …”
Section: Resultsmentioning
confidence: 88%
“…This illustrates that the nanostructure could reduce the reaction barriers and improve the catalytic performance. 48,49 It is well known that the higher gas hourly space velocity (GHSV), the more economical operation. The results in Figure 5d reveal the catalytic performance of Cu 0.75 Mn 2.25 O 4 -NH under different GHSV (30 000−70 000 h −1 ) conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Team of Professor Li from Dalian University of Technology [46] proposed that the sulfation tends to have a negative effect on the low-temperature reaction of FeVOx catalyst, but actively promotes high-temperature activity by inhibiting harmful NH3 oxidation. Li et al [47] found that V−W/Ce/Ti-5% presented better NH3-SCR activity and higher NH4HSO4 resistance at 280°C when 5% WO3 was loaded.…”
Section: Vanadium-based Catalystsmentioning
confidence: 99%